The Effect of Whole-Body Cryotherapy at Different Temperatures on Proinflammatory Cytokines, Oxidative Stress Parameters, and Disease Activity in Patients with Ankylosing Spondylitis. (3rd October 2018) - Straburzyńska-Lupa, Anna; Kasprzak, Magdalena Paulina; Romanowski, Mateusz Wojciech; Kwaśniewska, Anna; Romanowski, Wojciech; Iskra, Maria; Rutkowski, Radosław
Abstract : Purpose . Patients with ankylosing spondylitis (AS) have increased production of proinflammatory cytokines, increased oxidants, and decreased antioxidant capacity. The aim of this study was to determine the effect of whole-body cryotherapy (WBC) at −110°C and −60°C, on disease activity, selected proinflammatory cytokines, and oxidative stress in patients with AS. Methods . Sixty-five patients with AS were recruited to one of three study procedures: WBC at −110°C, −60°C, or exercise therapy (non-WBC). The Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), Ankylosing Spondylitis Disease Activity Score (ASDAS-CRP), concentration of C-reactive protein (CRP), and the concentrations of interleukin 8 and 17 (IL-8, IL-17) were measured at the beginning of the study and at the end of the intervention. The concentration of thiobarbituric acid reactive substances (TBARS), as a lipid peroxidation result, and total antioxidant status, an antioxidant organism potential, were measured. Results . All the studied groups showed significantly decreased posttherapy disease activity expressed as a function of the BASDAI, ASDAS-CRP, and the IL-8 concentration. We found that the TBARS concentration after therapy was significantly increased in the WBC at −110°C group. A comparison of the therapeutic effects between the treatment groups showed a significantly lower BASDAI after therapy in the WBC at −110°C group compared to the non-WBC group. Conclusion . WBC at −110°C had a positive effect on lowering AS clinical activity as measured by the BASDAI.